Direct nitrogen fixation at the edges of graphene nanoplatelets as efficient electrocatalysts for energy conversion - Jeon, In-Yup (Nature Publishing Group, 2013)
Nitrogen fixation is essential for the synthesis of many important chemicals (e.g., fertilizers, explosives) and basic building blocks for all forms of life (e.g., nucleotides for DNA and RNA, amino acids for proteins). However, direct nitrogen fixation is challenging as nitrogen (N(2)) does not easily react with other chemicals. By dry ball-milling graphite with N(2), we have discovered a simple, but versatile, scalable and eco-friendly, approach to direct fixation of N(2) at the edges of graphene nanoplatelets (GnPs). The mechanochemical cracking of graphitic C−C bonds generated active carbon species that react directly with N(2) to form five- and six-membered aromatic rings at the broken edges, leading to solution-processable edge-nitrogenated graphene nanoplatelets (NGnPs) with superb catalytic performance in both dye-sensitized solar cells and fuel cells to replace conventional Pt-based catalysts for energy conversion.